Computer Kinesiology: New Diagnostic and Therapeutic Tool for Lower Back Pain Treatment (Pilot Study) - Honcu, Pavla; Zach, Petr; Mrzilkova, Jana; Jandova, Dobroslava; Musil, Vladimir; Celko, Alexander Martin (BioMed research international, 2020)
The aim of this study was to demonstrate the effectiveness of the diagnostic and therapeutic medical information system Computer Kinesiology in physiotherapy in patients with low back pain who were not responding to conventional therapy. Computer Kinesiology is primarily intended for the diagnostics and therapy of functional disorders of the locomotor system. This pilot study population included 55 patients (Group 1) with acute and chronic back pain and 51 persons (Group 2) without back pain. The third group was a control group of 67 healthy volunteers with no evidence of musculoskeletal pathologies and no back pain. All 173 subjects were examined three times by the diagnostic part of the Computer Kinesiology method. Groups 1 and 2 were treated after every diagnostics. Group 3 was not treated. The effect was evaluated by H score. Improvements after therapy were defined by reducing the H score by at least 1 point. In Group 1, the H score decreased by at least 1 point in 87.3% (95% CI: 75.5-94.7) and in Group 2 in 78.4% (95% CI: 64.7-88.7). There was no change of distribution of H Score grade in Group 3. The improvement neither depended on gender, age, and BMI nor was it influenced by the length of the therapy. This study demonstrated a high therapeutic efficacy of the Computer Kinesiology system in patients with back pain (Group 1) and in persons without back pain (Group 2) who used the Computer Kinesiology system for primary and secondary prevention of back pain.
Keywords: expertní systémy; Diagnosis, Computer-Assisted; Humans; Primary Prevention; Case-Control Studies; kineziologie aplikovaná; lidé středního věku; diagnóza počítačová; studie případů a kontrol; Female; mladý dospělý; dospělí; výsledek terapie; primární prevence; lidé; Low Back Pain; pilotní projekty; Pilot Projects; Physical Therapy Modalities; Adult; ženské pohlaví; Male; Middle Aged; sekundární prevence; lumbalgie; Treatment Outcome; Czech Republic; Young Adult; techniky fyzikální terapie; Česká republika; mužské pohlaví; Expert Systems; Kinesiology, Applied; Secondary Prevention